Alguns gestores de fundos de ações são melhores do que outros? Uma análise cross-sectional das características dos gestores e do desempenho dos fundos - Ribeiro, Lizie Maria de Oliveira (2009)
The field of investment funds has been growing a lot in Brazil in the last 7 years. Such a movement can be seen at the percentual given to the stock funds. Part of this movement can be credited to the entrance of actors with no knowledge on the financial universe, but who mesmerize this segment as an opportunity to invest their money. The unknown work of the financial universe makes the new investor elect some criteria for the selection of where to put their resources, since it is expected a professional manager to make the best choices. According to Chevalier & Ellison (1999), the financial press produces a big number and variety of information the people who manage these funds, but little is spoken about their educational records. This work aims at analyzing if the performance of the stock funds is related to the features of the managers of those funds. Specifically, we studied the relationship between the performance of the funds and the degree of the managers, the quality of the schools where they studied, as well as the fact of having Lato Sensu or Stricto Sensu Graduation, besides their age and their 'experience time' in the financial market. We use as reference the data collected by the QUANTUN AXIS system (Quantun Assessment of the Investment Funds) having the period from september/2007 to 2008 as reference. We observed the résumés of 81 managers of the sample by searching sites of administrative companies, calling their numbers and résumés from information sites such as Bloomberg. Then, the Cross-Section analysis was made. For that, a chain of investigation was used which analyzed the impact of the educational records of the fund managers on their results in The U.S.A., emphasizing the work of Golec (1996), Chevalier & Ellison (1999) and Gottesman & Morey (2006). The result of this jog suggests that there is a difference in the cross-sectional analysis between the performance of the stock funds in Brazil and the quality of the manager’s college. Future researches could, using the same sample of managers, follow the evolution of the résumé data comparing to the performance of the funds managed in a time perspective using the panel data.